Molecular Signatures Correlated With Poor IVF Outcomes: Insights From the mRNA and lncRNA Expression of Endometriotic Granulosa Cells - Shi, Libing; Wei, Xianjiang; Wu, Bingbing; Yuan, Chunhui; Li, Chao; Dai, Yongdong; Chen, Jianmin; Zhou, Feng; Lin, Xiang; Zhang, Songying (Frontiers in Endocrinology, 2022)
The outcomes of IVF (in vitro fertilization) for endometriotic women are significantly worse than for patients without ovarian endometriosis (OEM), as shown by fewer retrieved oocytes. However, the exact pathophysiological mechanism is still unknown. Thus, we conducted a prospective study that analyzed mRNA and lncRNA transcriptome between granulosa cells (GCs) from patients with fewer retrieved oocytes due to OEM and GCs from controls with male factor (MF) infertility using an RNA sequencing approach. We found a group of significantly differentially expressed genes (DEGs), including NR5A2, MAP3K5, PGRMC2, PRKAR2A, DEPTOR, ITGAV, KPNB1, GPC6, EIF3A, and SMC5, which were validated to be upregulated and negatively correlated with retrieved oocyte numbers in GCs of patients with OEM, while DUSP1 demonstrated the opposite. The molecular functions of these DEGs were mainly enriched in pathways involving MAPK signaling, Wnt signaling, steroid hormone response, apoptosis, and cell junction. Furthermore, we performed lncRNA analysis and identified a group of differentially expressed known/novel lncRNAs that were co-expressed with the validated DEGs and correlated with retrieved oocyte numbers. Co-expression networks were constructed between the DEGs and known/novel lncRNAs. These distinctive molecular signatures uncovered in this study are involved in the pathological regulation of ovarian reserve dysfunction in OEM patients.